2020
DOI: 10.1088/1757-899x/830/2/022068
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ground Granulated Blast Furnace Slag (GGBFS) on Portland cement type II to compressive strength of high quality concrete

Abstract: Failure of concrete in the environment which containing sulphate causes damage to the cement bonds. One of environment that contains sulphate is peatlands. Peat water has a low acidity (pH) that it can damage the concrete slowly from the edges and corners with release of granules and becomes a porous. On this research, Ground Granulated Blast Furnace Slag (GGBFS) is a mineral additive that used as an additive to reduce the damage. The purpose of this research was to determine the effect of using variations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Green concrete terus dikembangkan untuk bahan pembangunan berkelanjutan dengan cara penerapan limbah industri untuk mengurangi polusi terhadap lingkungan (Puspita, 2020). Beton nanomaterial adalah beton generasi baru yang terbentuk dari material dengan ukuran butir berskala nano.…”
Section: Pendahuluanunclassified
“…Green concrete terus dikembangkan untuk bahan pembangunan berkelanjutan dengan cara penerapan limbah industri untuk mengurangi polusi terhadap lingkungan (Puspita, 2020). Beton nanomaterial adalah beton generasi baru yang terbentuk dari material dengan ukuran butir berskala nano.…”
Section: Pendahuluanunclassified
“…FA does not have the ability to bind particles or aggregates like cement, but with the fines size and presences of water in mix design, then SiO2 contained in FA will react chemically with Ca(OH)2 which formed by hydration process of cement and produces a substance that has bind ability. [5] Due to characteristics of both materials, many research by scientists had been developed and found many benefit of those material for substitute or partial replacement of cement such environmental friendly (due to reusing a waste material), increasing resistance to sulphate / chloride [6]- [10], reducing bleed rates [11], increasing compressive strength [2], [8], [12]- [15], increasing durability [8], [13], [16], and reducing permeability of concrete [8].…”
Section: Introductionmentioning
confidence: 99%